THE SOURCE OF LAWS IN THE GAMBIAN AND INDONESIAN LEGAL SYSTEM: A COMPARATIVE STUDY - Essa Garba; Azhari Yahya (Universitas Syiah Kuala, 2023)
This article compares the source of legal system in the Gambia with the legal system in Indonesia by looking at the similarities and differences between the two countries legal systems. In this paper, we use a normative juridical approach, it was found that the elements in the source of the legal system, in general both the Gambia and Indonesia have similarities, in terms of their adoption of a practical mixed system, of constituting the colonial laws, Customary law and Islamic law as part of their source of legal. The results also indicate differences between the Gambian and Indonesia legal system when it comes to the foundation of their legal system. The article suggest that Gambian and Indonesian legal experts should help in making more research on comparative studies of their countries. Conducting comparative studies will help in advancing the countries legal system for better service for their people respectively and update to modern development.